Estrategias de mitigación ante la ocurrencia de eventos adversos (antrópicos y naturales) a partir de Evin (evaluación inicial de necesidades) en la carrera de ingeniería ambiental – UTC. - Salguero Castro, Fernando Alexander (2021)
The research carried out in this work aims to protect people’s health and safety, based on strategies that will allow us to act correctly in the presence of phenomena both caused from natural origin or by humans actions. Cotopaxi province is a place prone to various disasters of both anthropic and natural origin. Around the time, it has been possible to verify the occurrence of adverse events in vulnerable areas; these have become a latent risk for the population of the site, which, since people do not have adequate knowledge in terms of prevention and mitigation in the answer of these events, they will not be able to give an effective response to situations that occur. This research work begins by identifying the most common anthropic and natural origin adverse events in Cotopaxi province, with the aim to assess the possible presence of this type of event in the study area (Salache Campus). Through techniques and methods, an information gathering will take place which will evaluate the initial needs of the study population, thus encompassing the understanding about how to act to face the certain present or possible adverse events; which represent a considerable risk for those involved individuals due to the possible negative impacts. Based on this, prevention and mitigation strategies will be developed in order to protect the health and safety of people against the occurrence of adverse events (anthropic and natural). This research will provide humanitarian assistance to students, teachers and people close to the study area, the same who through this research will have supported the information that will be necessary for the proper action in response of adverse events, safeguarding in this way physical, mental and emotional health of the people who are in constant risk because of the vulnerability existing in the place.